If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(7v + -7) + 5v = -87 Reorder the terms: -4(-7 + 7v) + 5v = -87 (-7 * -4 + 7v * -4) + 5v = -87 (28 + -28v) + 5v = -87 Combine like terms: -28v + 5v = -23v 28 + -23v = -87 Solving 28 + -23v = -87 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -23v = -87 + -28 Combine like terms: 28 + -28 = 0 0 + -23v = -87 + -28 -23v = -87 + -28 Combine like terms: -87 + -28 = -115 -23v = -115 Divide each side by '-23'. v = 5 Simplifying v = 5
| 2x^2-20x+100=108 | | 5x+3y+2z=4 | | 2(10)+3y=24 | | 2(x+3y)+4(x+5y)-3x= | | (42+2x)=(3x+4) | | 2(10.4)+3y=24 | | -2(y-3)=-6y-12+2y | | 3a+12a=-7 | | 7.5a+9.2-6.8a-11b= | | -6(-1-3x)=-120 | | 9x^3+54x^2= | | 9x+3x=24 | | 4(2y-10)=3(2y+8) | | 3(5x+1)-2=3y+6 | | -2(y-3)=-6y-12+12y | | 4x-9y+3x= | | 3(y-10)+1=-5.5(y-8) | | X^2-5-35=0 | | -9(x-6)-4=50 | | -10x=-27x-17 | | x+3(1.25)=7.25 | | (4a-3b)(2a+6b)= | | 5xt-3xy= | | h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= | | 10(2-m)-5(1-3m)=30 | | 0.53+0.34t=3.44t-0.71 |